2017
DOI: 10.1038/ncomms15122
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis proteins with a transposon-related domain act in gene silencing

Abstract: Transposable elements (TEs) are prevalent in most eukaryotes, and host genomes have devised silencing strategies to rein in TE activity. One of these, transcriptional silencing, is generally associated with DNA methylation and short interfering RNAs. Here we show that the Arabidopsis genes MAIL1 and MAIN define an alternative silencing pathway independent of DNA methylation and short interfering RNAs. Mutants for MAIL1 or MAIN exhibit release of silencing and appear to show impaired condensation of pericentrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
84
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(93 citation statements)
references
References 49 publications
9
84
0
Order By: Relevance
“…In Arabidopsis , two genes MAIL1 and MAIN encode related proteins that appear to be evolutionarily derived from a subset of Ty3/ gypsy retrotransposons found in angiosperms [48]. These proteins might have been initially captured from the host by these elements, but appear to have been reclaimed to partake in an epigenetic silencing pathway that transcriptionally represses a broad array of TEs [48].…”
Section: Host-te Conflict Resolved Through Te Domesticationmentioning
confidence: 99%
See 2 more Smart Citations
“…In Arabidopsis , two genes MAIL1 and MAIN encode related proteins that appear to be evolutionarily derived from a subset of Ty3/ gypsy retrotransposons found in angiosperms [48]. These proteins might have been initially captured from the host by these elements, but appear to have been reclaimed to partake in an epigenetic silencing pathway that transcriptionally represses a broad array of TEs [48].…”
Section: Host-te Conflict Resolved Through Te Domesticationmentioning
confidence: 99%
“…These proteins might have been initially captured from the host by these elements, but appear to have been reclaimed to partake in an epigenetic silencing pathway that transcriptionally represses a broad array of TEs [48]. Genetic loss of these genes resulted in impaired condensation of pericentromeric heterochromatin and upregulation of TE transcription suggesting their protein products are acting as transcriptional repressors.…”
Section: Host-te Conflict Resolved Through Te Domesticationmentioning
confidence: 99%
See 1 more Smart Citation
“…The main-2 and mail1-1 null mutants show similar developmental phenotypes, and transcriptomic analyses have revealed that many TEs, including ATCOPIA28 , are overexpressed in these two mutants (S2A and B Fig, and S2 Table) [17]. In addition, several genes are misregulated in the two pmd mutants (S2C and D Fig, and S2 Table).…”
Section: Resultsmentioning
confidence: 99%
“…More recently, the A. thaliana plant mobile domain (PMD) proteins MAINTENANCE OF MERISTEM (MAIN) and MAIN-LIKE 1 (MAIL1) were identified as new factors required for TE silencing [17]. In addition, these two proteins have been involved in genome stability, and regulation of developmental processes such as cell division and differentiation [18, 19].…”
Section: Introductionmentioning
confidence: 99%